2016
DOI: 10.1021/acs.langmuir.6b01467
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Soluble Surfactants on the Kinetics of Thinning of Liquid Bridges during Drops Formation and on Size of Satellite Droplets

Abstract: The results of an experimental study on thinning and breakage of liquid bridges during detachment of a drop from the tip of a capillary are presented for a series of surfactant solutions (including cationic, anionic, and nonionic surfactants) over a broad range of molecular masses, values of critical micelle concentration, and concentrations. The used experimental protocol revealed that the kinetics of the bridge thinning depends much more on the dynamics of adsorption at the surface of the drop before it dest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 35 publications
4
20
0
Order By: Relevance
“…Craster et al [9] have studied the breakup of a viscous thread in the presence of soluble surfactant at concentrations that are potentially above the critical micelle concentration and have shown that Marangoni stresses cause the formation of large satellites. This prediction was observed experimentally by Kovalchuk et al [22,23] where the satellite drop size increased by up to three times when soluble surfactant was added; the diffusion from the bulk to the interface has also been studied experimentally by Roche et al [42]. Craster et al [9] have also shown that the scalings for the minimum neck radius and axial velocity as the breakup singularity is approached are the same as the ones derived by Eggers [11] as surfactant is swept away from the thinning region.…”
Section: Introductionsupporting
confidence: 83%
“…Craster et al [9] have studied the breakup of a viscous thread in the presence of soluble surfactant at concentrations that are potentially above the critical micelle concentration and have shown that Marangoni stresses cause the formation of large satellites. This prediction was observed experimentally by Kovalchuk et al [22,23] where the satellite drop size increased by up to three times when soluble surfactant was added; the diffusion from the bulk to the interface has also been studied experimentally by Roche et al [42]. Craster et al [9] have also shown that the scalings for the minimum neck radius and axial velocity as the breakup singularity is approached are the same as the ones derived by Eggers [11] as surfactant is swept away from the thinning region.…”
Section: Introductionsupporting
confidence: 83%
“…The addition of glycerol practically does not influence the interfacial tension of surfactant solutions at concentrations above CMC (Kovalchuk et al, 2016(Kovalchuk et al, , 2018. This was confirmed also by our measurements giving interfacial tension of 30 mM solutions of SDS and C12TAB in 60% glycerol/40% water mixture with mineral oil around 9 mN/m, close to interfacial tension of solutions in water.…”
Section: Transition From Periodic Dripping To Irregular Regimessupporting
confidence: 86%
“…The concentration is normalised by the corresponding values of CMC: 8.2 mM for SDS and 15 mM for C 12 TAB. Addition of salt results in a decrease of CMC value, therefore for composition SDS + NaBr the CMC values, c CMC have been calculated using the equation reported previously (Kovalchuk et al, 2016;Anon, 2001):…”
Section: Effect Of Electric Field On Drop Size At Periodic Drippingmentioning
confidence: 99%
See 1 more Smart Citation
“…20,21 Roché et al showed that the dynamic interfacial tension controlled by the surfactant led to the changes of the neck thinning rate. 22 Kovalchuk et al pointed out that the dynamic interfacial tension during the formation process depended on the adsorption kinetics of the surfactant at the surface of the droplet [23][24][25][26] and the effect of the surfactant on the transition between ow regimes correlated with the dynamic surface tension. Kamat et al demonstrated by the simulation and experiment that Marangoni stresses resulting from the nonuniformity of surfactant concentration on the interface led to reduced thread thinning rate and formation of multiple satellites.…”
Section: Introductionmentioning
confidence: 99%